(untitled) (Research, Society and Development, 2024)
The integrative approach in public health has stood out as an effective strategy in treating chronic non-communicable diseases (NCDs), offering complementary alternatives to traditional methods and promoting improved quality of life. NCDs, such as cardiovascular diseases and cancer, represent a global challenge for health systems. Integrating phytotherapy in NCDs treatment considers people’s physical, emotional, social, and environmental aspects, promoting a more comprehensive and patient-centered approach. This study aims to present ways of controlling non-communicable diseases with herbal medicines for your health. Bibliographic review research was carried out and, for this purpose, scientific databases such as Scielo, Scopus, Web of Science, LILACS, and PubMed were consulted. The health descriptors used were: "phytotherapy", and "non-communicable diseases". The results indicate that the use of herbal medicines can be beneficial in controlling diseases such as diabetes, hypertension, cardiovascular diseases, and obesity. The pharmacological properties of medicinal plants, such as antihyperglycemic, antioxidant, and anti-inflammatory activities, contribute to preventing and effectively treating these conditions. Furthermore, herbal medicine offers a more accessible and less invasive alternative to synthetic medicines, which is particularly relevant for low-income populations.